Neuroprotective Mechanism of MOTS-c in TBI Mice: Insights from Integrated Transcriptomic and Metabolomic Analyses - Li F; Jia Y; Fang J; Gong L; Zhang Y; Wei S; Wu L; Jiang P (Dove Medical Press, 2024)
Fengfeng Li,1 Yang Jia,1 Jun Fang,2 Linqiang Gong,3 Yazhou Zhang,4 Shanshan Wei,5 Linlin Wu,6 Pei Jiang5 1Neurosurgery Department, Tengzhou Central People's Hospital Affiliated to Xuzhou Medical University, Tengzhou, Shandong, 277500, People's Republic of China; 2Anesthesiology Department, Tengzhou Central People's Hospital Affiliated to Xuzhou Medical University, Tengzhou, Shandong, 277500, People's Republic of China; 3Gastroenterology Department, Tengzhou Central People's Hospital Affiliated to Xuzhou Medical University, Tengzhou, Shandong, 277500, People's Republic of China; 4Foot and Ankle Surgery Department, Tengzhou Central People's Hospital Affiliated to Xuzhou Medical University, Tengzhou, Shandong, 277500, People's Republic of China; 5Translational Pharmaceutical Laboratory, Jining First People's Hospital, Jining, Shandong, 272000, People's Republic of China; 6Oncology Department, Tengzhou Central People's Hospital Affiliated to Xuzhou Medical University, Tengzhou, Shandong, 277500, People's Republic of ChinaCorrespondence: Linlin Wu, Oncology Department, Tengzhou Central People's Hospital Affiliated to Xuzhou Medical University, Tengzhou, Shandong, 277500, People's Republic of China, Tel +86 632-5513457, Email linlinliff@163.com Pei Jiang, Translational Pharmaceutical Laboratory, Jining First People's Hospital, Jining, Shandong, 272000, People's Republic of China, Tel +86 537-2106208, Email jiangpeicsu@sina.comBackground: Traumatic brain injury (TBI) is a condition characterized by structural and physiological disruptions in brain function caused by external forces. However, as the highly complex and heterogenous nature of TBI, effective treatments are currently lacking. Mitochondrial open reading frame of the 12S rRNA-c (MOTS-c) has shown notable antinociceptive and anti-inflammatory effects, yet its detailed neuroprotective effects and mode of action remain incompletely understood. This study investigated the neuroprotective effects and the underlying mechanisms of MOTS-c.Methods: Adult male C57BL/6 mice were randomly divided into three groups: control (CON) group, MOTS-c group and TBI group. Enzyme-linked immunosorbent assay (ELISA) kit method was used to measure the expression levels of MOTS-c in different groups. Behavioral tests were conducted to assess the effects of MOTS-c. Then, transcriptomics and metabolomics were performed to search Differentially Expressed Genes (DEGs) and Differentially Expressed Metabolites (DEMs), respectively. Moreover, the integrated transcriptomics and metabolomics analysis were employed using R packages and online Kyoto Encyclopedia of Genes and Genomes (KEGG) database.Results: ELISA kit method showed that TBI resulted in a decrease in the expression of MOTS-c. and peripheral administration of MOTS-c could enter the brain tissue after TBI. Behavioral tests revealed that MOTS-c improved memory, learning, and motor function impairments in TBI mice. Additionally, transcriptomic analysis screened 159 differentially expressed genes. Metabolomic analysis identified 491 metabolites with significant differences. Integrated analysis found 14 KEGG pathways, primarily related to metabolic pathways. Besides, several signaling pathways were enriched, including neuroactive ligand-receptor interaction and retrograde endocannabinoid signaling.Conclusion: TBI reduced the expression of MOTS-c. MOTS-c reduced inflammatory responses, molecular damage, and cell death by down-regulating macrophage migration inhibitory factor (MIF) expression and activating the retrograde endocannabinoid signaling pathway. In addition, MOTS-c alleviated the response to hypoxic stress and enhanced lipid β-oxidation to provide energy for the body following TBI. Overall, our study offered new insights into the neuroprotective mechanisms of MOTS-c in TBI mice.Keywords: MOTS-c, TBI, transcriptomics, metabolomics, neuroprotective